Pengaruh Angka KemiskinPengaruh Angka Kemiskinan Terhadap Angka Tuberculosis di Indonesia (Studi Kasus 6 Provinsi di Pulau Jawa) an Terhadap Angka Tuberculosis di Indonesia (Studi Kasus 6 Provinsi di Pulau Jawa) - Ni Nengah Rizki Noventy; I Wayan Suparta (Journal on Education, 2023)
The essence of this study is to determine the effect of tuberculosis rates in Indonesia. The purpose of this study was to determine whether the human development index, the number of poor people, the gross regional domestic product and the air quality index affect the tuberculosis rate in Indonesia (a case study of 6 provinces in Java Island). This type of research used is secondary data quantitative research. The data used in this study is panel data which is a combination of time series and cross section data. This study uses time series data which is annual data for 6 years, namely from 2016 to 2021. The method of analysis in this study uses the panel data regression method, the benefits or advantages of using panel data regression, steps to determine panel models, testing classical assumptions, testing hypotheses and test the coefficient of determination (R2) by processing data using Eviews 10. Based on partial analysis in the Case Study of 6 Provinces in Java Island, it was found that the human development index, gross regional domestic product, and air quality index had a negative and significant effect on tuberculosis rates in Indonesia while the number of poor people has a positive and significant effect on the tuberculosis rate in Indonesia. Based on the simultaneous analysis that all observed variables have a significant effect on tuberculosis rates in Indonesia.